Overexpression of PDSS2-Del2 in HCC promotes tumor metastasis by interacting with macrophages - Guanghui Li; Daqin Suo; Yuanzhen Ma; Tingting Zeng; Jiarong Zhan; Yunfei Yuan; Xin-Yuan Guan; Yan Li (Cell Death Discovery)
Abstract Hepatocellular carcinoma (HCC) is one of the most frequent solid tumors worldwide. According to the Global Cancer Statistics 2020, liver cancer remains the third cause of cancer death globally. Despite significant advances in systemic therapy, HCC still has one of the worst prognoses due to its frequent recurrence and metastasis. Previously we found that PDSS2-Del2 (prenyl diphosphate synthase subunit 2 with exon 2 deletion), a novel variant of PDSS2, could promote HCC metastasis and angiogenesis via activating NF-κB. In this study, we elucidate a novel mechanism by which PDSS2-Del2 enhances HCC metastasis. The overexpression of PDSS2-Del2 in HCC cells promotes the ubiquitination and degradation of SKOR1, consequently heightening SMAD3 phosphorylation. Subsequently, the expression and secretion of MST1 (macrophage stimulatory protein 1) are upregulated, resulting in enhanced recruitment of macrophages into tumor tissues where they differentiate into M2-type macrophages. Co-culture with PDSS2-Del2 overexpressed HCC cells activated the PI3K/AKT signaling pathway in macrophages, and more MMP2 and MMP9 were secreted, which facilitated HCC cell dissemination. Our study elucidates a novel molecular mechanism by which PDSS2-Del2 promotes HCC metastasis, which may contribute to the development of effective HCC clinical treatment and prevent tumor metastasis. Furthermore, MST1 could be a potential therapeutic target, and MST1 inhibitors might be integrated into clinical practice for HCC patients with high expression of PDSS2-Del2.